Almost famous: Peter Woodcock, media framing, and obscurity in the cultural construction of a serial killer - Hier, Sean P. (Crime, media, culture, 2020)
This article contributes to criminological research on cultural constructions of serial murderers by investigating the little-known Canadian case of Peter Woodcock. There is a tacit scholarly consensus that news media routinely sensationalize modern serial killers as celebrity monsters. The case of Woodcock aligns with a different theoretical trajectory geared toward explaining the relative obscurity of otherwise ?made for primetime? serial murder events. Examining coverage in the local and national press, the article builds on the sparse literature concerned with absences in conventional explanations for how news media participate in the cultural construction of serial murderers. It does so by gleaning insights into the ways in which Woodcock was simultaneously framed as a sadistic sex maniac responsible for killing three young children in the 1950s and a victim of social circumstance owing to his troubled upbringing. Although Woodcock killed before the rise of the serial killer claims-making industry in the 1980s, the article concludes by reflecting on the curious absence of a retroactively reconstructed modern melodramatic storyline in light of the surreal characteristics of the investigation leading up to his arrest and the circumstances that enabled him to gruesomely kill again in 1991.